Pengujian Level Kreativitas Pada Siswa Berdasarkan Skala Kekuatan dan Kebajikan Karakter dan Tes Kreativitas Verbal - Zulmi Ramdani; Bagus Hary Prakoso; Silmi Amrullah; Lidwina Felisima Tae; Feri Indra Irawan (Universitas Andalas, 2018)
Creativity is an important aspect in building a good culture of education. Good creativity is shown by the learning outcomes that not only focus on improving cognitive abilities but also on the process of solving a problem either by using divergent or convergent thinking skills. This study was carried out with descriptive quantitative. The study was conducted using two instruments, namely the creativity character scale consisting of 10 items and a set of Verbal Creativity Tests (TKV) consisting of six subtests. The total subjects involved in this study were 470 students who were divided into groups that got the character scale of creativity with the group given the verbal ability test. The results of the study, either through the creativity character scale or verbal creativity tests, show the acquisition of creativity scores which describes that there are still many individuals who have not been optimized in terms of creativity. This becomes a serious concern that can be anticipated by providing information about the importance of creativity. It is also built by creating an instrument that is more effective directly capturing the condition of one's creativity as a whole.